2015
DOI: 10.1186/s12909-015-0517-9
|View full text |Cite
|
Sign up to set email alerts
|

A pilot Tuning Project-based national study on recently graduated medical students’ self-assessment of competences - the TEST study

Abstract: BackgroundThe Tuning Project is an initiative funded by the European Commission that developed core competences for primary medical degrees in Europe. Students' grouped self-assessments are used for program evaluation and improvement of curricula. The TEST study aimed to assess how do Portuguese medical graduates self-assess their acquisition of core competences and experiences of contact with patients in core settings according to the Tuning framework.MethodsTranslation of the Tuning's competences (Clinical P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…A study in Nepal also recommended continuing professional development for doctors on procedural skills and public health tasks [ 25 ]. However, our findings differ from a Portuguese study which claimed that doctors demonstrated sufficient level of procedural and public health competencies [ 19 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A study in Nepal also recommended continuing professional development for doctors on procedural skills and public health tasks [ 25 ]. However, our findings differ from a Portuguese study which claimed that doctors demonstrated sufficient level of procedural and public health competencies [ 19 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Another study in Western Europe reported that general practitioners had gate keeping roles and wider scope of work [ 18 ]. A Portugal based study found out that over 80% of new doctors had managed few surgical, obstetric, gynaecologic and emergency patients [ 19 ]. A study from Vietnam showed that psychiatry, ophthalmology, and gynecology and obstetrics were infrequently performed [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the residents differed in the areas where they felt ready. These findings support the studies that reveal the opinions of students, 37 supervisors, 38 specialist registrars and consultant opinions. 39 Preparing graduates for their professional responsibilities will reduce the inequality between what they expect as a physician and what they contribute to the profession.…”
Section: Discussionsupporting
confidence: 89%
“…Various curricular initiatives have been developed to improve the acquisition of research skills by Health Science students [ 18 , 19 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ] but these are rarely discussed by the students themselves, although creating opportunities for authentic inquiry and metacognitive reflection are two of the most important pedagogical practices to help students think like scientists [ [38] , [39] , [40] ].…”
Section: Discussionmentioning
confidence: 99%
“…In response to involve future HP in scientific research, curricular initiatives have been developed to improve the acquisition of research skills in undergraduate medical and, by extension, Health Science students [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. These skills, which consist of the ability to detect a problem, collect sufficient data relevant to the problem from reliable sources, evaluate and effectively apply those data to solve the problem, have been progressively framed in terms of global competencies [ 31 ] as it is considered that the future will be shaped by the adoption of competencies to specific contexts of information and knowledge [ 3 , 31 ].…”
Section: Introductionmentioning
confidence: 99%